Stoicism PhilosophyIbn Qayyim Al-Jawziyyah: A Proposal for a Quarter Life Crisis Solution - Zidha Khira Himmah; Yeti Dahliana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Stoicism is a philosophy that emphasizes self-control, acceptance of fate, and the achievement of inner peace, offering a relevant perspective for addressing the quarter-life crisis. Ibn Qayyim Al-Jawziyyah, a prominent scholar in Islamic tradition, holds views aligned with Stoicism through his teachings on patience and reliance on God. The quarter-life crisis itself is a psychological crisis typically experienced by individuals in their 20s to 30s, characterized by confusion, anxiety, and uncertainty regarding life purpose and the future. This research aims to analyze Ibn Qayyim Al-Jawziyyah's thoughts within the framework of Stoicism and how his teachings can serve as a spiritual solution to the quarter-life crisis. The research employs a qualitative approach with a descriptive-analytical method. The primary sources are his works, such as Madarij As-Salikin and Zad al-Ma'ad, alongside Stoicism literature as a comparison. This study finds significant similarities between Stoicism and Ibn Qayyim Al-Jawziyyah's thoughts, especially in terms of accepting fate and self-control. The teachings of sabr and tawakkul advocated by Ibn Qayyim prove relevant as practical solutions to help individuals achieve inner peace and emotional stability when facing a quarter-life crisis.